A Pedagogy of Faith: The Theological Vision of Paulo Freire - Aryoubi, Hogai (In Factis Pax: Journal of Peace Education and Social Justice, 2023)
A Pedagogy of Faith: The Theological Vision of Paulo Freire by Irwin Leopando, Bloomsbury, 2017, 237 pp.